1987
DOI: 10.1172/jci112821
|View full text |Cite
|
Sign up to set email alerts
|

Galactose ingestion increases vascular permeability and collagen solubility in normal male rats.

Abstract: In view of the similarity of cataracts and neuropathy in galactosefed and diabetic rats, the present experiments were undertaken to determine whether consumption of galactose-enriched diets (10, 25, or 50% by weight) also increases collagen crosslinking and permeation of vessels by 125I-albumin analagous to that observed in diabetic rats. The observations in these experiments: (a) demonstrate that consumption of galactose-enriched diets for 3 wk selectively increases '25I-albumin permeation of the same vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The increases in granulation tissue polyol levels and 125 Ialbumin permeation of granulation tissue vessels, as well as the decreased plasma levels of IGF-I, in sham-operated diabetic rats (vs. sham-operated nondiabetic rats) are consistent with previous observations in this animal model (20)(21)(22)(23)(24)28). The finding that granulation tissue polyol levels fell dramatically in 2-day insulin-pump diabetic rats and did not differ significantly from those of 2-day sham-operated control rats is consistent with the normalization of plasma glucose levels in these rats as well as with numerous reports demonstrating that the polyol content of cells and tissues is related to ambient glucose levels in vivo and that polyol levels increase during incubation of cells and tissues in vitro in media containing high concentrations of glucose (14)(15)(16)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increases in granulation tissue polyol levels and 125 Ialbumin permeation of granulation tissue vessels, as well as the decreased plasma levels of IGF-I, in sham-operated diabetic rats (vs. sham-operated nondiabetic rats) are consistent with previous observations in this animal model (20)(21)(22)(23)(24)28). The finding that granulation tissue polyol levels fell dramatically in 2-day insulin-pump diabetic rats and did not differ significantly from those of 2-day sham-operated control rats is consistent with the normalization of plasma glucose levels in these rats as well as with numerous reports demonstrating that the polyol content of cells and tissues is related to ambient glucose levels in vivo and that polyol levels increase during incubation of cells and tissues in vitro in media containing high concentrations of glucose (14)(15)(16)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, increased polyol metabolism in diabetic animals has also been linked to the development of morphological (17)(18)(19) and functional (20)(21)(22)(23)(24)(25) changes in the microvasculature. The effect of rapid normalization of glycemia on polyol metabolism and vascular function in diabetic rats is unknown.…”
mentioning
confidence: 99%
“…Malmgren et al (19), Jakobsen et al (22), Sima and Robertson (23), and Powell et al (15) found no changes in bloodnerve barrier permeability to protein tracers such as albumin or horseradish peroxidase. On the other hand, increased blood-nerve barrier permeability in diabetic patients and diabetic and galactosemic animals has been reported by other investigators (20,21,(24)(25)(26). One possible reason for these conflicting results is that the change in blood-nerve barrier permeability of diabetic and galactosemic animals is subtle and difficult to detect with morphological techniques involving large protein tracers (27).…”
mentioning
confidence: 97%
“…This could perhalps be related to a gradLual increcase in blood nerve barrier permeability (Chang, Tomlinson, Jeffrey, Tilton. Sherman, Ackeriman, Bergei, Cicero, Kilo & Williamson, 1987) allowing greater galactitol clearance. Fructose was slightly reduced in galactosaemic animnals, presumably because of competitioni by galactose reducing the flux of glucose through the polyol pathwxay.…”
mentioning
confidence: 99%